Validity and reliability of a kinematic device for measuring the force developed during squatting - Rahmani, A.; Dalleau, G.; Viale, F.; Hautier, C. A. (Journal of Applied Biomechanics, 2000)
This study determined the validity and reliability of the kinematic device developed by Bosco et al. (1995) by comparing its peak force, peak velocity, and peak power measurements to data obtained simultaneously with a force platform placed under the subject`s feet. Fifteen international downhill skiers performed maximal half-squats on a guided barbell with masses of 60-180 kg. The coefficient of correlation (r) between the two peak forces (r = 0.85-0.95, p < .001), the two peak velocities (r = 0.74-0.91, p < .001), and the two peak powers (r = 0.85-0.95, p < .001) indicated that the kinematic device measurements were valid. The trial-to-trial reliability of half-squat exercises measured by the kinematic device gave an intraclass coefficient of correlation (CR) of: 0.70-0.90 for peak force, 0.62-0.90 for peak velocity, and 0.57-0.91 for peak power. There were no statistical differences between the two trials. The standard error of the means (SEM%) was less than 5% for peak force, less than 4% for peak velocity, and less than 7% for power. The high CR and low SEM% indicate that the kinematic device is reliable. The movement recorded by the kinematic device accurately described the action measured by the force platform. Mit der Studie wurde die Validität und Reliabilität des kinematischen Gerätes untersucht, das Bosco et al. (1995) entwickelt worden war. Dazu wurden die Spitzenwerte der Geschwindigkeit, Kraft und Leistung mit den Werten verglichen, die von Probanden ermittelt wurden, die diese gleichzeitig mittels Kraftmessplatform unter ihren Füssen erreichten. 15 alpine Skiläufer der internationalen Klasse absolvierten geführte halbe Kniebeugen mit einer Last von 60 bis 180 kg auf einer Hantelstange aus. Der Korrelationskoeffizient (r) zwischen den beiden Maximalwerten der Kraft (r=0.85 - 0.95, p < .001), den beiden Maximalwerten der Geschwindigkeit (r=0.74 - 0.91, p< .001) und den Maximalwerten der Leistung (r=0.85 - 0.95, p<.001) gaben Hinweise darauf, dass die Messungen mit dem kinematischen gerät valide waren. Die Versuch-zu-Versuch-Reliabilität der halben Kniebeugen und der dabei ermittelten Messwerte ergaben einen Intraklassen-Korrelationskoeffizienten (CR) von 0.70 - 0.90 für die Maximalwerte der Kraft, von 0.62 - 0.90 für die Maximalwerte der Geschwindigkeit und von 0.57 - 0.91 für die Maximalwerte der Leistung. Zwischen den beiden Versuchen wurden keine statitischen Differenzen festgestellt. Der Standardfehler der Durchschnittswerte (SEM%) lag unter 5% für die Maximalkräfte, unter 4% für die Maximalgeschwindigkeit und unter 7% für die Maximalleistung. Der hohe CR und niedrige SEM% weist darauf hin, dass das kinematische Gerät verlässliche Ergebnisse liefert. Die vom kinematischen Gerät aufgezeichnete Bewegung beschrieb genau die Aktion, die von der Kraftmessplatform beschrieben wurde.